May 17: International day against Homophobia, Transphobia and Biphobia in Georgia Abstract - Kevkhishvili, Mariana (Politics / პოლიტიკა, 2022)
The International Day against Homophobia, Transphobia, and Biphobia is observed in Georgia on May 17 to condemn violence and express solidarity with LGBTQI+ people. However, it is primarily associated with violent actions that endanger people's safety. The purpose of this paper is to investigate Georgia's practice of commemorating May 17, the International Day against Transphobia, Homophobia, and Biphobia. Attempts to commemorate May 17 in Georgia began in 2009, and the first May 17 march was held in 2012. The month of March 2013 proved to be a watershed moment in the process of commemorating this date. Clergymen and parishioners confronted and dispersed the LGBTQI+ people who had gathered on Rustaveli Avenue. The state failed to ensure the safety of those gathered there, as well as their freedom of expression, and then failed to identify and punish the criminals. The Catholicos-Patriarch of Georgia, Ilia II, declared May 17 to be the day of family sanctity. Due to a lack of security, members of the LGBTQI+ community were unable to gather publicly to express their views in the next coming years. The locations of small rallies and events organized as part of the May 17 celebrations are usually announced to the media and supporters a few hours in advance. To this day, the main issue is the state's inconsistent and ill-considered policy toward these processes, which is why measures aimed at raising public awareness, which would help to break existing stereotypical attitudes, are not implemented.
Keywords: May 17, LGBTQI+, Discrimination, Georgia.